Peningkatan Kemampuan Bina Diri Melalui Media Audio Visual pada Anak Tunagrahita Ringan - Hendri, Suci Khairani; marlina, Marlina; Damri, Damri (Jurnal Pendidikan Kebutuhan Khusus, 2019)
This research was based on the problem that was found by the researcher at Special School Luak Nan Bungsu and Special School Peduli Anak Bangsa Payakumbuh grade VI that mild mental retardation students faced problem in self development learning in using bandage. It was proved from the researcher?s observation that students can not use bandage independently. The purpose of this research was to prove the effectiveness of using tutorial video media compared with power point media to improve self development ability of mild mental retardation students at Special School Luak Nan Bungsu and Special School Peduli Anak Bangsa Payakumbuh. The result of this research, the using of tutorial video media was more effective than power point media to improve self development of mild mental retardation students at Special School Luak Nan Bungsu Payakumbuh. The researcher suggests that teachers to guide mild mental retardation students in using bandage independently.